Study on Biogas Production from Organic Waste of Food Leftovers and Garden Waste Using Green Phoskko 7 in a Fixed Dome Biodigester at PT Asmin Bara Bronang: Studi Pembentukan Biogas dari Sampah Organik Sisa Makanan dan Sisa Taman Menggunakan Green Phoskko 7 Pada Biodigester Fixed Dome di PT Asmin Bara Bronang - Az'zahra Nuzula Husaeni; Gina Lova Sari; Kania Ratnawati; Mohammad Akbar Ogy Darmawan (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This study aims to evaluate biogas production from a mixture of food waste and garden waste using a fixed dome biodigester with GP-7 activator. Observed parameters include initial pH, temperature, and carbon-to-nitrogen (C/N) ratio. The fermentation was carried out for 30 days under anaerobic conditions. Results showed an initial pH of 7.00, temperature of 37.70 °C, and a C/N ratio of 24.41, which are within the optimal range. However, storage for ±15 days increased the C/N ratio to 33.31 due to nitrogen loss. Biogas volume increased sharply, peaking at 4.85 m³ on day 20, then declined to 0 m³ by the end of the fermentation period. This pattern reflects the microbial growth phases and the efficiency of organic matter conversion into gas. The study confirms that initial substrate characteristics and retention time play crucial roles in optimizing biogas production from organic waste in industrial environments.